PHARMACOEPIDEMIOLOGICAL AND PHARMACOECONOMIC STUDIES OF ANTIHYPERTENSIVE TREATMENT IN RUSSIA. Analytical Review - T. S. Romanenko; A. V. Kontsevaya; S. V. Fitilev (Столичная издательская компания, 2015)
The article reviews the pharmacoepidemiological and pharmacoeconomic trials of antihypertensive therapy, conducted during the last decades inRussia. Despite the increased interest to the issue of cost-effectiveness of arterial hypertension treatment in recent years, in most cases researches carried out in this area are characterized by the using of simple methods of pharmacoeconomic analysis, taking into account only the direct costs, as well as determining of the drugs cost-effectiveness in clinical trials, and not in real clinical practice.